Pemanfaatan Kegemaran, Sosial Media, dan E-Commerce dalam Persaingan Usaha Mikro Kecil Menengah Di Era Digital: Study Deskriptif pada Pororo Official - Priyanka, Felyna (Journal of Economics and Business Research (JUEBIR), 2024)
Social media is something that is very close to society in the digital era. Through social media, people can communicate with anyone in one direction or two ways without any distance. With social media, people can filter whatever they want to see, whether in the form of images or videos. One of them is the large number of funny videos featuring cats, making many people now love these cute furry animals. Many cat lovers also follow cat accounts on social media. Many cat owners and also cat social media admins are taking advantage of their passion for selling cat-themed products. Starting from being known on social media to opening online shops in e-commerce. This of course has a good impact on society because of the economic turnaround. The aim of this research is to explain the role of passion, social media and e-commerce in the competitive advantage of micro, small and medium enterprises in the digital era. The method used in this research is a qualitative method with observation and review of supporting documents. It is hoped that the results of this research will provide new knowledge about the importance of utilizing hobbies, social media and e-commerce in the competitive advantage of small bussiness.